BIOMECHANICAL PROPERTIES OF BLOOD FLOW AND IMPACT ON THE CARDIOVASCULAR SYSTEM (Prima Journal of Integrated Studies, 2026)
In progress blood of the flow main biomechanical features , including viscosity , Poiseuille Reynolds 's law turbulence criteria and vein of the wall elasticity in detail seeing Blood is released . of the flow disorders with related cardiological pathologies and their prevent to take methods analysis will be done.
Keywords: biomechanics , blood flow , viscosity , rheology , artery , Reynolds number , atherosclerosis , cardiovascular vein system , hemodynamics.